THE FACTOR OF STUDENTS’ ATTITUDE TO PHYSICAL EXERCISES IN THE CONTEXT OF EVALUATION AND SELF-ASSESSMENT OF PHYSICAL ABILITIES - Вржесневский, І. І. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article is devoted to the study of the factor of students’ attitude to physical exercises in relation to self-assessment of physical abilities. An attempt to reveal the influence of self-evaluation of personal ability on the formation or correction of students’ attitude toward individual physical training is made. The answers to eight questions of the survey, the results of the methodical task of the module test of individual physical activity and attitude to corporeality are presented and analyzed. Based on the results of the study, it was suggested that the declared attitude of students is demonstrative, and the true one is regulated on an unconscious level and is ambivalent in nature.